Genotyping reveals high genotypic diversity and potential migration pattern of Puccinia striiformis f. sp. tritici populations in Xinjiang and Northwest epidemic regions of China - Jianing Zhu; Muhammad Awais; Maxinzhi Liu; Zejian Li; Jinbiao Ma; Lan Wang; Jie Zhao; Zhensheng Kang (Phytopathology Research)
Abstract The Xinjiang epidemiological region of wheat stripe rust, caused by Puccinia striiformis f. sp. tritici (Pst), exhibits distinct characteristics compared to other epidemic regions in China. This region provides favorable conditions for Pst to complete its life cycle and serves as a connection to other major wheat-growing areas across the country. However, despite limited studies on Pst populations in Xinjiang, a comprehensive understanding of the epidemiology of wheat stripe rust in this region remains unclear. This gap complicates the effective management of the disease due to uncertainties regarding inoculum sources and migration routes. In this study, we conducted a comparative population genetic analysis of Pst populations within Xinjiang (North, Midwest, and East Xinjiang) and neighboring provinces (Gansu, Shaanxi, and Ningxia) to trace inoculum origins and confirm migration patterns. For this purpose, a total of 232 samples were collected and genotyped using 17 simple sequence repeats markers. Our findings revealed significant gene flow within the Midwestern and Eastern Xinjiang regions, as well as among the neighboring provinces of Gansu, Qinghai, Ningxia, and Shaanxi. The Midwestern Xinjiang, particularly its western subregion, is likely to be an inoculum source. Additionally, we observed limited gene flow and shared multilocus genotypes between Xinjiang and its neighboring provinces. The overall high genotypic diversity observed in Northwestern China (Simpson’s index = 0.98) indicates a hotspot for the emergence of new Pst races through sexual recombination. This is likely driven by the widespread distribution of the alternate host, barberry (Berberis spp.), which facilitates the sexual reproduction of Pst in certain regions. These results provide valuable insights into the gene flow dynamics of Pst populations in Xinjiang and its neighboring provinces. Furthermore, this study underscores the importance of deploying genetically resistant wheat cultivars to effectively control wheat stripe rust in these regions.